Estudo cromossômico da tribo Dalbergieae sensu Klitgaard & Lavin (2005) com ênfase no clado Dalbergia s. str. (Leguminosae, Papilionoideae) : Chromosome studies of the tribe Dalbergieae sensuKlitgaard & Lavin (2005) with emphasis on Dalbergia sensu strictoclade (Leguminosae, Papilionoideae) - Polido, Caroline do Amaral, 1983- (2013)
Orientadores: Eliana Regina Forni Martins, Ana Paula de Moraes